2012
DOI: 10.1007/s11524-012-9758-7
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Walkability and Active Travel (Walking and Cycling) in New York City

Abstract: Urban planners have suggested that built environment characteristics can support active travel (walking and cycling) and reduce sedentary behavior. This study assessed whether engagement in active travel is associated with neighborhood walkability measured for zip codes in New York City. Data were analyzed on engagement in active travel and the frequency of walking or biking ten blocks or more in the past month, from 8,064 respondents to the New York City 2003 Community Health Survey (CHS). A neighborhood walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 35 publications
7
76
0
2
Order By: Relevance
“…Our findings are in line with those of other research studies Freeman et al, 2013;Grasser, Van Dyck, Titze, & Stronegger, 2013), which confirmed that higher territorial walkability increases the AC of the inhabitants. The average proportion of AC among the inhabitants of Liberec city (17%) is low compared with a study of Swedish adults (22.2%), which included a total of 16,705 individuals aged 18-80 years (Lindström, 2008).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are in line with those of other research studies Freeman et al, 2013;Grasser, Van Dyck, Titze, & Stronegger, 2013), which confirmed that higher territorial walkability increases the AC of the inhabitants. The average proportion of AC among the inhabitants of Liberec city (17%) is low compared with a study of Swedish adults (22.2%), which included a total of 16,705 individuals aged 18-80 years (Lindström, 2008).…”
Section: Discussionsupporting
confidence: 94%
“…The proportion of active and passive commuting by education towards the outskirts). This is consistent with the findings and results gathered in other studies (Christiansen, Madsen, Schipperijn, Ersbøll, & Troelsen, 2014;De Meester et al, 2012;Frank et al, 2010;Freeman et al, 2013). Adams et al (2014) concluded that areas with high walkability are characterized by an accumulation of a large number of inhabitants and higher commuting accessibility (e.g., Hong Kong or Bogota in Colombia).…”
Section: Discussionsupporting
confidence: 91%
“…In this measure, the total walkability score is the sum of zscores of five measures derived from urban planning literature: (1) residential population density, (2) land use mix, (3) intersection density, (4) retail floor area ratio, and (5) subway stop density. This measure has previously been shown to predict BMI [33], engagement in active transport [34], and total physical activity as recorded by accelerometer [35].…”
Section: Neighborhood Measuresmentioning
confidence: 99%
“…In addition, many previous studies focus on relatively low-density suburban contexts in Western countries, except for a few studies that have focused on a highdensity built environment such as New York City (Freeman et al, 2013;Lovasi et al, 2012). Some studies have stated that the relationships between the built environment and walking activity are complicated due to spatial heterogeneity, self-selection issues such as attitudes and perceptions on walking behavior, and methodological differences (Chatman, 2009;Feuillet et .…”
Section: Literature Reviewmentioning
confidence: 99%